2011
DOI: 10.5251/abjna.2011.2.8.1187.1193
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of some Nigerian spices on some pathogens

Abstract: The aqueous and ethanol extracts of four spices ( Monodora myristica, Piper guineense, Xylopia aethiopica, Tetrapleura tetraptera ) were prepared and the antibacterial properties assessed using the agar diffusion method. The test organisms were Enterohaemorrhagic E.coli, Shigella, Salmonella, Klebsiella, Pseudomonas, Klebsiella pnemonium, Staphylococcus aureus, Staphylococcus aureus (ATCC 25923), Bacillus sp. and Enterococcus faecalis. The susceptibility of the test bacteria strains to various antibiotics wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 12 publications
4
22
0
3
Order By: Relevance
“…This finding is not in agreement with Ebana et al [12] who reported the inability of ethanolic extract of P. guineense to inhibit P. aeruginosa, while aqueous extract did. Aboaba et al [15] and Anyanwu and Nwosu [11] however, reported the inhibition of P. aeruginosa by both the aqueous and ethanol extract of P. guineense, with the ethanol zones of inhibition comparable to the finding of this study. The finding of this study is in agreement with reports by Osuala and Anyadoh [34] that methanolic extracts of P. guineense exhibited much more antibacterial activity against P. aeruginosa than the ethanolic extracts, recommending that methanol be used in preference to ethanol in extracting active ingredients from plants.…”
Section: Antibacterial Activity Of P Guineensesupporting
confidence: 78%
“…This finding is not in agreement with Ebana et al [12] who reported the inability of ethanolic extract of P. guineense to inhibit P. aeruginosa, while aqueous extract did. Aboaba et al [15] and Anyanwu and Nwosu [11] however, reported the inhibition of P. aeruginosa by both the aqueous and ethanol extract of P. guineense, with the ethanol zones of inhibition comparable to the finding of this study. The finding of this study is in agreement with reports by Osuala and Anyadoh [34] that methanolic extracts of P. guineense exhibited much more antibacterial activity against P. aeruginosa than the ethanolic extracts, recommending that methanol be used in preference to ethanol in extracting active ingredients from plants.…”
Section: Antibacterial Activity Of P Guineensesupporting
confidence: 78%
“…These values are used as guide for the treatment of most infections (Aboaba et al 2011). This study implies that T. vulgaris could be used as spice and also exhibit antibacterial effect on contaminated seafoods.…”
Section: Discussionmentioning
confidence: 93%
“…Sensitivity of the Vibrio species to T. vulgaris extracts have shown that the spice extract can be used as a complement to the array of antimicrobial compounds available. According to Aboaba et al (2011) the inhibitory zones shown by some of the spices can be comparable to chemotherapeutic drugs. The MIC values can also be used as a guide for the treatment of most infections (Aboaba et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations